The Effect of The Team-Assisted Individualization Learning Model on Students' Science Process Skills and Cognitive Learning Outcomes - Mardiati Mardiati; I Wayan Karmana (PAIDAGOGIA: Jurnal Inovasi Pendidikan dan Pembelajaran, 2024)
This study aims to determine the influence of the Team Assisted Individualization (TAI) learning model on students' science process skills and cognitive learning outcomes. Employing a quasi-experimental design with a nonequivalent control group design, the research population consists of all tenth-grade students at Madrasah Aliyah Qamarul Huda Bagu, Central Lombok, with a sample size of 49 individuals. Observation sheets are utilized to measure science process skills, while students' cognitive learning outcomes are assessed through a learning achievement test. The data on science process skills are tabulated and categorized as follows: high (80-100%), medium (60-79%), and low (0-59%). The student's learning outcomes are tabulated and analyzed using covariance (ANCOVA) analysis to discern differences between the experimental and control classes. Implementing the TAI model in teaching effectively enhances science process skills and students' learning outcomes (Sig.<.05). The students' science process skills fall within the medium category. Successful TAI implementation requires meticulous planning, teacher support, and coordination among team members. Additionally, factors such as group size, students' proficiency levels, and available resources can influence the effectiveness of TAI in education. Hence, educators must carefully consider TAI implementation in the classroom to maximize its impact on student motivation and cognitive learning outcomes.